Diaspora and Implementation of Sheikh Yusuf al-Makassarī’s Religious Moderation Teachings in South Sulawesi and Kalimantan - Sahib, Muzdalifah; Irnawati, Irnawati; Sahib, Muh. Amin; Asiah, Nur; Sahib, Nur Faizah; Jappie, Saarah (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2024)
Sheikh Yusuf al-Makassarī (1626-1699) is a worldwide figure from Gowa-Makassar, South Sulawesi, Indonesia, a reformer in the Islamic mystical world and a moderate ṣứfī whose teachings spread among his followers up today. This research investigates the diaspora and dissemination of Sheikh Yusuf al-Makassarī’s teachings on religious moderation in South Sulawesi and Kalimantan. Employing a qualitative descriptive method and a phenomenological approach, the study seeks to elucidate the process of diaspora development, assess the perceptions of al- Makassarī’s followers, especially Ṭarīqa Khalwatiyya Yusufiyya followers regarding religious moderation, and analyze the implementation of his teachings. The findings of this research reveal that the diaspora of al-Makassarī’s religious moderation teachings has emanated and proliferated from Gowa through three teachers (murshids) and his descendants (1940s-2022), notably Sheikh K.H. Sahib Sultan (d.2022), and his parents across South Sulawesi and Kalimantan, extending even to the entirety of the archipelago. Throughout four to five generations, the diaspora has become entrenched through these murshids. While a significant portion of al-Makassarī’s followers may remain unfamiliar with the term